1975
DOI: 10.1139/y75-041
|View full text |Cite
|
Sign up to set email alerts
|

Thermal, Metabolic, and Cardiovascular Responses to Various Degrees of Cold Stress

Abstract: The metabolic, thermal, and cardiovascular responses of two male Caucasians to 1 2 h exposure to ambient temperature ranging between 28 degrees C and 5 degrees C were studied and related to the respective ambient temperatures. The metabolic heat production increased linearly with decreasing ambient temperature, where heat production (kcal times m- minus 2 times h- minus 1) = minus 2.79 Ta degrees C + 103.4, r = -0.97, P smaller than 0.001. During all exposures below 28 degrees C, the rate of decrease in mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
24
0

Year Published

1990
1990
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 13 publications
7
24
0
Order By: Relevance
“…With regard to blood pressure, part of the observed rise seems to stem from a fall in temperature (Keatings & McCance, 1957) and its impact on peripheral resistance (Raven et al, 1970;Raven et al, 1975). Another potentially important`seasonal' risk factor is ®brinogen, which tends to rise in the winter (Van der Bom et al, 1997).…”
mentioning
confidence: 99%
“…With regard to blood pressure, part of the observed rise seems to stem from a fall in temperature (Keatings & McCance, 1957) and its impact on peripheral resistance (Raven et al, 1970;Raven et al, 1975). Another potentially important`seasonal' risk factor is ®brinogen, which tends to rise in the winter (Van der Bom et al, 1997).…”
mentioning
confidence: 99%
“…[3][4][5] This is particularly visible in persons who Note: ABF = alternative blood flow; BI = base impedance; CT = crest time; CW = crest width; HR = heart rate; IR = impedance ratio; SR = slope ratio. Note: ABF = alternative blood flow; BI = base impedance; CT = crest time; CW = crest width; HR = heart rate; IR = impedance ratio; SR = slope ratio.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…The multi-city Monica study [22] also reported findings consistent with those of our study, as have chamber studies on modest cold exposure. [18,19] Given that increased BP is a known risk factor of cardiovascular mortality and morbidity, these findings suggest that increase in blood pressure could be related to cold-induced cardiovascular mortality.…”
Section: Discussionmentioning
confidence: 95%
“…The effects of mild exposure to cold have been tested under controlled conditions, and the results have shown that short-term exposure to cold causes subcutaneous vasoconstriction that increases central blood volume that further increases BP. [18,19] However, the effects of temperature on BP under ambient conditions with changing air pressure and humidity, which may also include intermittent exposures as people go in and out of buildings, may differ substantially from those in chamber studies, and are not thoroughly studied. Two epidemiological studies from Europe have reported that systolic BP [20], or both systolic and diastolic blood pressure [21] decrease in association with increasing outdoor temperature.…”
Section: Introductionmentioning
confidence: 99%